2014
DOI: 10.4314/tjpr.v13i9.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant Activities of Ya-hom Intajak, a Thai Herbal Formulation, and its Component Plants

Abstract: FRAP (r = 0.908, p < 0.01) and DPPH activities (r = 0.648, p < 0.01

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
4
18
0
Order By: Relevance
“…In previous studies, the methanolic macerate of Anacyclus clavatus flowers yielded about 6,78 ± 0,23% [18]. Whereas, the A. pyrethrum ethanolic macerate, from Spain and India, recorded yields of 4,34% and 11,53% respectively [19,20]. In fact, rare works mentioned the yields of the different fractions prepared according to our methodology.…”
Section: Yield Of Phenolic Extractsmentioning
confidence: 80%
See 1 more Smart Citation
“…In previous studies, the methanolic macerate of Anacyclus clavatus flowers yielded about 6,78 ± 0,23% [18]. Whereas, the A. pyrethrum ethanolic macerate, from Spain and India, recorded yields of 4,34% and 11,53% respectively [19,20]. In fact, rare works mentioned the yields of the different fractions prepared according to our methodology.…”
Section: Yield Of Phenolic Extractsmentioning
confidence: 80%
“…It also seems that the hydromethanolic extracts of the aerial and subterranean parts respectively of A. clavatus (Algeria) and A. pyrethrum (India) had a phenol content of 71,09 ± 3,84 and 62,89 ± 0,43 mg EAG/g extract respectively [23,24]. As a reminder, ethanolic extracts from roots of the same species, A. pyrethrum from India and Spain, were found to be rich in total polyphenols estimated at 159,63 ± 0,52 and 42,21 ± 1,59 mg EAG/g extract respectively [19,25].…”
Section: Dosage Of Total Phenolsmentioning
confidence: 94%
“…Previously, antioxidant property of C.sappan was investigated and reported that the activity was according to the phenolic compounds (19) such as alkaloid, tannins, steroids, and flavonoids (14,20), which most of flavonoid compounds in the extracts are flavone and flavonol (21). Most of these compounds are not soluble in water.…”
Section: Discussionmentioning
confidence: 99%
“…Nine additional articles were identified through manual searches of the references, bibliographies and consultations with experts. This yielded 24 articles which met the inclusion criteria including 2 in vitro cell lines or bacteria (Sripanidkulchai et al, 2007;Tepsuwan et al, 2011), 3 in vitro cell-free (Channarong et al, 2012;Nalinratana et al, 2014;Tuekaew et al, 2014), 5 in vitro animal tissue studies (Chantharangsikul et al, 2009;Nonthasawadsri et al, 2015;Nusuetrong et al, 2012;Pataloong and Sawasdimongkol, 1995;Suvitayavat et al, 2005b), 13 in vivo animal studies (Chavalittumrong et al, 2009;Intayoong, 2006;Jariyapongskul et al, 2006;Kengkoom and Ampawong, 2015;Kengkoom et al, 2012;Matangkasombat, 1974;Nernpermpisooth et al, 2015;Sirisangtragul and Sripanidkulchai, 2013;Sirisangtrakul and Sripanidkulchai, 2011;Suvitayavat et al, 2004;Suvitayavat et al, 2005a;Thongpraditchote et al, 1999) and 1 human study (Suvitayavat et al, 2005) (Fig 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…Cell-free studies rated Yahoms as moderately high phenolic content as judged by as high reducing capacities (Channarong et al, 2012;Nalinratana et al, 2014;Tuekaew et al, 2014) (Table 3). But how these translate to the in vivo environment is unclear.…”
Section: Pharmacological Effects Of Yahommentioning
confidence: 99%